Cardiac lymphoma in dog - Cruz, G. D.; Souza, T. V.; Cruz, A. M.; Trizzine, L. G. D. (Scientific Electronic Archives, 2016)
Lymphoma is a lymphoid tumor that originates in hematopoietic organs such as lymph node, spleen or liver. In dogs, the overall prevalence of cardiac tumors was estimated to be only 0.19% based on the results of the survey of a large database, and lymphomas accounts for approximately 2% of all cardiac tumors. In general, the involvement of the myocardium is rarely described in canine lymphoma. Currently, there is no evidence of a viral association with primary cardiac lymphoma in dogs, but other types of immunosuppression may contribute to abnormal events, such as involvement primary cardiac. The aim of this study was to analyze a case of sudden death of a bitch, SRD, aged 10, who had the final diagnosis of cardiac lymphoma.